Komitmen Biodiversity Beyond National Jurisdiction (BBNJ) Indonesia Terkait dengan Pengelolaan Hasil Sedimentasi Laut di Pulau Bintan Kepulauan Riau - Mustika Sukma Utari; Andrea Octora Yama Satria (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
This article examines the implementation of Indonesia’s international commitments regarding Biodiversity Beyond National Jurisdiction (BBNJ). It focuses on the management of marine sedimentation under Government Regulation No. 26 of 2023, with Bintan Island as one of the areas designated for sand mining permits. A normative legal approach was taken in this article, examining international legal instruments such as UNCLOS 1982, as well as Indonesia’s domestic regulations on the ratification of BBNJ through Presidential Regulation No. 67 of 2025. Analysis of other instruments, such as legal doctrines, case studies, and scholarly literature, also serves as a method of analysis in this article. Indonesia’s commitment to the BBNJ aligns with UNCLOS 1982, which calls for the conservation of all marine resources, particularly those falling under the “common heritage of mankind.” The management and utilization of marine sedimentation resources hold great economic promise. The four main stages of marine sediment management outlined in Government Regulation No. 26 of 2023 must comply with applicable regulations. This is due to the potential for misconduct and procedural discrepancies in technical operations on-site, which could cause fatal damage to marine life. International commitments such as UNCLOS 1982 and the BBNJ play a crucial role in this regard. As a balancing factor in the implementation of development goals and international conservation responsibilities .